2021
DOI: 10.1037/tra0000931
|View full text |Cite
|
Sign up to set email alerts
|

Americans’ distress early in the COVID-19 pandemic: Protective resources and coping strategies.

Abstract: Objective:The rapid emergence of the coronavirus disease 2019 (COVID-19) pandemic in the United States has dramatically altered daily life and taken a toll on Americans' physical, mental, social, and financial well-being. Based on previous widespread disasters, future high prevalence of short-and long-term adverse mental health consequences are anticipated. Studies of COVID-19 outside the United States indicated moderately high levels of distress, but we have little information regarding Americans' distress no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 56 publications
1
68
0
5
Order By: Relevance
“…In Table 1, we report some examples of studies of coping strategies that can be coded according to this classification. Some studies have recently examined how adults coped during the pandemics, exploring the links between coping strategies and some indicators of positive psychological functioning and/or psychopathological symptoms (Fullana et al, 2020;Wakashima et al, 2020;Bakker and van Wingerden, 2021;Park et al, 2021;Shamblaw et al, 2021). Shamblaw et al (2021) explored adaptive strategies in a sample of American adults and found that a variety of strategies, such as active coping, positive reframing, planning, acceptance, emotional support, and the use of informational support was associated with lower levels of depression and higher levels of quality of life.…”
Section: Psychological Functioning Coping Strategies and Pandemicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 1, we report some examples of studies of coping strategies that can be coded according to this classification. Some studies have recently examined how adults coped during the pandemics, exploring the links between coping strategies and some indicators of positive psychological functioning and/or psychopathological symptoms (Fullana et al, 2020;Wakashima et al, 2020;Bakker and van Wingerden, 2021;Park et al, 2021;Shamblaw et al, 2021). Shamblaw et al (2021) explored adaptive strategies in a sample of American adults and found that a variety of strategies, such as active coping, positive reframing, planning, acceptance, emotional support, and the use of informational support was associated with lower levels of depression and higher levels of quality of life.…”
Section: Psychological Functioning Coping Strategies and Pandemicsmentioning
confidence: 99%
“…However, being relatively cheap to implement and easy to be adapted to many different contexts, self-report instruments are still the most commonly used tools for accessing individuals' inner worlds. Most of the published studies for assessing coping strategies related to COVID-19 used self-report questionnaires (e.g., Fullana et al, 2020;Wakashima et al, 2020;Bakker and van Wingerden, 2021;Park et al, 2021;Shamblaw et al, 2021) and only a few utilized open-ended questions with content analysis (e.g., Son et al, 2020;Waselewski et al, 2020). Generally, researchers who studied disaster-related coping strategies did not develop specific measures focused on disasters.…”
Section: Measurement Of Disaster-related Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasaulinė COVID-19 pandemija yra viena iš didžiausių mūsų laikų sveikatos apsaugos krizių, kuri vienu ar kitu būdu paveikė beveik kiekvieną žmogų. Dėl pandemijos sukeltos krizės politikai, sveikatos apsaugos darbuotojai, mokslininkai, verslininkai ir kiti susidūrė su visiškai naujais iššūkiais (pvz., didžiuliu situacijos neapibrėžtumu, informacijos trūkumu, taikomu karantinu, ekonominėmis problemomis, poveikiu žmonių fizinei, psichinei, socialinei ir finansinei gerovei) (Daumann, Follert, 2020;Nielsen, Levkovich, 2020;Park et al, 2021).…”
Section: įVadasunclassified
“…Nuo COVID-19 pandemijos pradžios praėjo santykinai nedaug laiko, tačiau tyrėjai jau skyrė nemažai pastangų įvairioms jos sukeltoms problemoms nagrinėti: a) sprendimų priėmimui neapibrėžtumo ir informacijos trūkumo sąlygomis (pvz., kaip reaguoti į staiga kilusią grėsmę žmonių sveikatai, kaip sumažinti koronaviruso plitimą, patiriamus ekonominius nuostolius ir pan.) (Comfort et al, 2020;Gleißner et al, 2021;Pappas, Glyptou, 2021;Sun et al, 2020); b) pandemijos sukeltiems psichologiniams padariniams (patiriamam stresui, nerimui, baimei, depresijai, sumažėjusiai subjektyviai gyvenimo kokybei arba gerovei), taip pat taikomiems įveikos būdams ir jų efektyvumui (Nielsen, Levkovich, 2020;Park et al, 2021;Shamblaw et al, 2021;Zacher, Rudolph, 2021); c) impulsyviam pirkimui pandemijos metu (Ahmed et al, 2020;Brizi, Biraglia, 2021;Laato et al, 2020;Naeem, 2021); d) žmonių ketinimui skiepytis arba skiepyti savo vaikus nuo koronaviruso, taip pat tokio ketinimo veiksniams (Neumann-Böhme et al, 2020;Goldman et al, 2020;Loomba et al, 2021;Reiter et al, 2020) ir pan.…”
Section: įVadasunclassified